A green approach of improving interface and performance of plant fibre composites using microcrystalline cellulose. (1st October 2018) - Pichandi, Subramani; Rana, Sohel; Parveen, Shama; Fangueiro, Raul
Graphical abstract: Highlights: Jute/epoxy hierarchical composites were developed using microcrystalline cellulose (MCC). MCC was dispersed in epoxy resin using a short ultrasonication treatment. Presence of MCC led to drastic improvement in the jute fibre-epoxy matrix interface. Mechanical performance of jute composites improved considerably due to MCC. Strong improvement in dynamic mechanical performance was also achieved. Abstract: In contrast to the conventional methods of improving interface and performances of plant fibre composites through fibre surface modification, this paper reports a novel approach based on the dispersion of microcrystalline cellulose (MCC) in the composite's matrix. MCC was dispersed within the matrix of jute fibre reinforced epoxy composites to improve the fibre/matrix interface as well as mechanical, dynamic-mechanical and thermal performances. To develop these novel jute/epoxy/MCC hierarchical composites, MCC was first dispersed within an epoxy resin using a short ultrasonication process (1 h) and subsequently, the MCC/epoxy suspensions were infused through jute fabrics using the vacuum infusion technique and cured. Hierarchical composites by dispersing multi-walled carbon nanotubes (MWCNTs) within the epoxy resin were also fabricated to compare their performance with MCC based hierarchical composites. Interface (single fibre pull-out test), mechanical (tensile, flexural, izod impact), thermal (thermogravimetric analysis) and dynamic mechanical performances of the developed composites were thoroughly studied. It was observed that the addition of MCC to the epoxy matrix led to a significant increase in the interfacial shear strength (IFSS) between jute fibres and the epoxy matrix and consequently, resulted up to 18.4%, 21.5%, 28.3%, 67% and 49.5% improvements in the tensile strength, flexural strength, impact energy, storage and loss moduli, respectively as compared to the neat jute/epoxy composites. The above improvements achieved with MCC were significantly higher as compared to the MWCNT based hierarchical composites developed using the same technique.